Answer:
(- 1, 2)
Step-by-step explanation:
Given a quadratic in standard form y = ax² + bx + c : a ≠ 0
Then the x- coordinate of the vertex is
= - ![\frac{b}{2a}](https://tex.z-dn.net/?f=%5Cfrac%7Bb%7D%7B2a%7D)
f(x) = x² + 2x + 3 ← is in standard form
with a = 1 and b = 2, hence
= -
= - 1
Substitute x = - 1 into f(x) for corresponding value of y
f(- 1) = (- 1)² + 2(- 1) + 3 = 1 - 2 + 3 = 2
vertex = (- 1, 2 )
Answer:
J. 1
Step-by-step explanation:
Plug the x values into the equation:
f(-1)=3-(-1)^2
f(2)=3-(2)^2
Solve each one, then add.
3-(-1)^2=
=3-1=2
3-(2)^2=
=3-4=-1
Combine the answers together.
2-1=1
The answer is J. 1.
Hope this helps!
Please mark as brainliest if correct!
Answer:
Step-by-step explanation:
Answer:
We have been given that PQ bisects . In the second statement of the given two-column proof, the statement is .
This implies that the two angles formed by bisection of angle by the line PQ are equal. We know that the reason for this is simple. It is the definition of bisection of an angle that the two smaller angles formed will be equal to each other.
Therefore, the reason for statement 2 of the given two column proof is c) Definition of bisect
Step-by-step explanation: